Generalized Winkler support properties for far field modeling of laterally vibrating piles - Bahrami, Amir; Nikraz, Hamid (Pergamon, 2017)
This paper presents a closed from solution to the governing elastodynamic equations of an infinitely long pile in homogeneous, elastic, semi-infinite half space soil. Furthermore the effects of shear stresses acting at soil-pile interface and axial force in the pile are also included in the analysis. The solution leads to an equivalent beam on generalized Winkler support model. This model is comprised of linear springs, masses and dampers. Values of stiffness, mass and damping are formulated for low and high frequency regimes. Static stiffness of the soil springs which is considered as zero frequency limit, showed good agreement with previously published values. Damping value are compared with previously published values with relatively good agreement. Possible applications of the theory for far field modeling of the soil is discussed.